The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/jlb.3ab0820-576rrr
|View full text |Cite|
|
Sign up to set email alerts
|

Baicalin protects mice from infection with methicillin-resistant Staphylococcus aureus via alleviating inflammatory response

Abstract: Sepsis was redefined as life-threatening organ dysfunction caused by a dysregulated host response to infection in 2016. One of its most common causes is Staphylococcus aureus, especially methicillin-resistant Staphylococcus aureus (MRSA), which leads to a significant increase in morbidity and mortality. Therefore, innovative and effective approaches to combat MRSA infection are urgently needed. Recently, host-directed therapy (HDT) has become a new strategy in the treatment of infectious diseases, especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Flavonoid-enriched extract from S. baicalensis root (FESR) modulated the inflammatory responses by increasing the level of IL-10 in influenza A virus-induced acute lung injury in mice, which was speculated to be due to BA, the most abundant compound in FESR ( Zhi et al, 2019 ). In addition, BA, the major ingredient of S. baicalensis , could inhibit the production of IL-6 and TNF-α but increase the level of IL-10 in serum after methicillin-resistant Staphylococcus aureus (MRSA)-stimulated inflammatory response in mice ( Shi et al, 2020 ). Similarly, in the present study, we also found that the levels of serum IL-1β, IL-6, and TNF-α were increased in DSS-induced colitis, while LSE supplementation could decrease these inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid-enriched extract from S. baicalensis root (FESR) modulated the inflammatory responses by increasing the level of IL-10 in influenza A virus-induced acute lung injury in mice, which was speculated to be due to BA, the most abundant compound in FESR ( Zhi et al, 2019 ). In addition, BA, the major ingredient of S. baicalensis , could inhibit the production of IL-6 and TNF-α but increase the level of IL-10 in serum after methicillin-resistant Staphylococcus aureus (MRSA)-stimulated inflammatory response in mice ( Shi et al, 2020 ). Similarly, in the present study, we also found that the levels of serum IL-1β, IL-6, and TNF-α were increased in DSS-induced colitis, while LSE supplementation could decrease these inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the application of functional additives in intestinal health care and disease control has been a research focus worldwide. BA is a flavonoid compound isolated from medicinal plants such as Scutellaria baicalensis ( Shi et al, 2020 ). Numerous studies have shown that BA has a variety of pharmacological effects, such as anti-inflammatory, antioxidant, and anticancer effects on the lung, uterus, and other organs ( Zhang et al, 2015 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…such as inhibiting or killing the pathogenic bacteria [72,73] (usually not as good as antibiotics), immune regulation [74,75], and anti-in ammatory activity [76]. Therefore, geraniol demonstrated a better mastitis cure rate with a longer course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This slow action is probably related to the characteristics of TCM. The compound kills the pathogenic bacteria directly and inhibits the pathogenic bacteria through immune regulation [75], anti-endotoxin [80], and antiin ammatory action [76]. Together, these observations suggest that geraniol can be used to treat cow mastitis more mildly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation